Analysis of Conceptual Understanding of Grade V Elementary School Students on Water Material through RADEC Learning - Harun, Gustiayu Juita; Sujana, Atep; Sopandi, Wahyu (International Conference on Elementary Education, 2022)
This research aimed to analyze the conceptual understanding of the fifth grade elementary school students on Water material through RADEC Learning. The method used was a qualitative approach with a qualitative descriptive design. The research subjects were fifth grade students in one of private elementary schools in the city of Bandung. The research data was collected with a test instrument. There were five test items used to obtain data on students conceptual understanding. The results of this study were that conceptual solving of students in grade V on water material through the RADEC learning model seen from grouping all results according to the dimensions of knowledge show that the RADEC model is good for helping students instill the dimensions of conceptual, metacognitive, and factual knowledge with successive percentages 81.78%, 79.31%, and 72.41%. Meanwhile, the procedural knowledge dimension obtained a percentage of 58.62%, meaning that the RADEC model was quite good at instilling the procedural knowledge dimension.